Without Words: Breathing Within the Echoes of Circular (Un)Certainty - MacKenzie-Dawson, Sarah (Art/Research International)

(untitled) (University of Alberta, 2022)
Our ways of seeing, of being, of knowing in the world are shaped by relationship. These relationships reflect the complex dynamic that exists as we navigate between the living layers of human nature, desire, loss, connection and disconnection, certainty and uncertainty. Across the space of this piece, I seek to breathe, to move with observant awareness through emotion and cognition. I want to acknowledge the deep sense of absence that reverberates across my consciousness, an absence that is both spiritual and etymological. This absence reflects the complexity of my subjectivity as a mother, an educator, one who navigates within the narrative of colonization, and a synchronicity of spirit that transcends self. It is through the breath that I find myself in rhythm, connected to the land—spirit, (be)longing with/in (un)certainty. Poetry, prose, and photographs intermingle upon the pages, offering an assemblage of being, of (un)knowing, of breathing amidst (im)permanence. This work creates space for me to better know myself as scholar, teacher, mother—as one who lives upon a stolen, sacred landscape, while creating openings for dialogue, disruption, and praxis.